An Easy-to-Fabricate, Submerged Carbon-Based Air Cathode for Biofuel Cells - Sukri, Asiah; Othman, Raihan; Sarifuddin, Norshahida (IIUM Engineering Journal, 2024)
An air cathode (AC) is one of the main components in an AC-based biofuel cell (BFC). Its cost accounts for nearly half of the total cost of the cell as specific requirements must be met for it to perform as an effective site for the oxygen (O2) reduction reaction (ORR) to occur. In most applications where the AC is totally submerged in the electrolyte, air or O2 is bubbled throughout the electrolyte during the entire discharge operation to enhance the cell performance. This is because the dissolved O2 (DO) concentration is merely one-third of the O2 concentration in ambient air. Unfortunately, this approach increases the overall complexity and cost of the system. Therefore, this present study developed an effective, easy-to-fabricate AC for use under totally submerged and unaerated conditions. The design principle of the proposed AC is a balance between the hydrophobicity and hydrophilicity of the components used, i.e., the combination of a carbon felt, an interwoven carbon fiber sheet, and a nickel mesh. All the cathode components were snugly fitted merely using the mechanical pressure of the cylindrical BFC holders. The fabricated AC was assembled in a zinc-air BFC employing fungal microbes Phanerochaete chrysosporium (P. chrysosporium). When tested at a constant current of 1.0 mA under unaerated, uncontrolled ambition conditions, the zinc-air BFC discharge lasted 42 days with an average operating voltage of 200 mV. Under these conditions and even without the inclusion of any catalytic material, the cell performance met the operating requirements of the low-powered remote sensing devices. Therefore, the proposed easy-to-fabricate submerged air electrode has demonstrated its viability for use in BFCs. ABSTRAK: Katod udara (AC) merupakan salah satu komponen utama bagi sel tenaga bio (SFB) berasaskan AC. Hampir separuh daripada keseluruhan kos sel berpunca dari katod udara (AC). Ini kerana beberapa keperluan khusus perlu dipenuhi bagi menyediakan tapak tindak balas penguraian (TPO) oksigen (O2) berlaku. Kebanyakan aplikasi biasa di mana AC terendam sepenuhnya dalam larutan elektrolit. Udara atau oksigen O2 dialirkan secara berterusan sepanjang operasi discaj bertujuan menggandakan prestasi sel. Ini disebabkan kepekatan oksigen terlarut adalah hanya sepertiga daripada kepekatan oksigen di dalam udara sekitar. Malangnya, kaedah ini akan menambah kompleksiti dan kos. Oleh itu, kajian ini bertujuan membina AC yang efektif, bersifat mudah-pasang bagi aplikasi tenggelam sepenuhnya dan tanpa pengudaraan. Prinsip asas pada cadangan rekabentuk katod udara AC ini adalah bagi mengimbangi ciri hidrofobik dan hidrofilik komponen yang digunakan, iaitu kombinasi fabrik karbon, lapisan serat karbon terjalin dan jaringan nikel. Kesemua komponen katod ini terangkum kemas menggunakan tekanan mekanikal pada selinder pemegang BFC. AC ini kemudiannya dikumpulkan dalam BFC zink-udara dengan mengguna pakai mikrob kulat Phanerochaete chrysosporium (P. chrysosporium). Apabila diuji dengan arus tetap 1.0 mA dalam keadaan tanpa udara dan sekitaran tanpa kawalan, sel BFC zink-udara mampu bertahan selama 42 hari dengan purata voltan operasi sebanyak 200 mV. Dalam kondisi ini dan walau tanpa sebarang unsur pemangkin, prestasi sel memenuhi keperluan operasi peranti penderiaan jauh bertenaga rendah. Oleh itu, katod udara yang dibangunkan bagi aplikasi elektrod terendam penuh dan bersifat mudah-pasang ini telah berhasil memenuhi keperluan bagi kegunaan BFC.